2020
DOI: 10.3390/cells9040858
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of STAT3 Signaling, Cell Redox Defenses and Cell Cycle Checkpoints by β-Caryophyllene in Cholangiocarcinoma Cells: Possible Mechanisms Accounting for Doxorubicin Chemosensitization and Chemoprevention

Abstract: Cholangiocarcinoma (CCA) is an aggressive group of biliary tract cancers, characterized by late diagnosis, low effective chemotherapies, multidrug resistance, and poor outcomes. In the attempt to identify new therapeutic strategies for CCA, we studied the antiproliferative activity of a combination between doxorubicin and the natural sesquiterpene β-caryophyllene in cholangiocarcinoma Mz-ChA-1 cells and nonmalignant H69 cholangiocytes, under both long-term and metronomic schedules. The modulation of STAT3 sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(66 citation statements)
references
References 109 publications
4
58
0
Order By: Relevance
“…This effect was found associated with an increased cell cycle arrest in G2/M phase, thus suggesting that as a consequence of the increased γH2AX by doxorubicin, β-caryophyllene stimulates G2/M checkpoint and DNA repair systems in order to block the cell cycle and enable restoring the genome integrity. This hypothesis is also supported by the evidence of a lower genoprotective effect in cholangiocarcinoma cells, which is likely due to the presence of defective DNA repair systems, as found in different cancer cells [ 163 ].…”
Section: Caryophyllane Sesquiterpenes In Cancer Chemopreventionmentioning
confidence: 70%
See 3 more Smart Citations
“…This effect was found associated with an increased cell cycle arrest in G2/M phase, thus suggesting that as a consequence of the increased γH2AX by doxorubicin, β-caryophyllene stimulates G2/M checkpoint and DNA repair systems in order to block the cell cycle and enable restoring the genome integrity. This hypothesis is also supported by the evidence of a lower genoprotective effect in cholangiocarcinoma cells, which is likely due to the presence of defective DNA repair systems, as found in different cancer cells [ 163 ].…”
Section: Caryophyllane Sesquiterpenes In Cancer Chemopreventionmentioning
confidence: 70%
“…Indeed, it has been characterized by a plethora of biological activities, among which analgesic, anti-inflammatory, antioxidant, neuroprotective, and antiproliferative were the most investigated; moreover, it has been reported to affect phospholipid cooperativity and membrane permeability ( Table 3 ). These properties have provided benefits in several experimental models of disease, such as neurodegeneration, inflammation, pain, anxiety, depression, autoimmune diseases, metabolic ailments, osteoarthritis and some cancer models [ 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 ,…”
Section: Caryophyllane Sesquiterpenesmentioning
confidence: 99%
See 2 more Smart Citations
“…al. have revealed that STAT-3 was constitutively activated in malignancy instead of normal tissues [35,36]. Interestingly, our results showed that genipin selectively suppressed HCC cells proliferation without signi cant toxicity in normal cells.…”
Section: Discussionmentioning
confidence: 58%